Doping of graphene induced by boron/silicon substrate. (2nd May 2017) - Dianat, Arezoo; Liao, Zhongquan; Gall, Martin; Zhang, Tao; Gutierrez, Rafael; Zschech, Ehrenfried; Cuniberti, Gianaurelio
Abstract: In this work, we show the doping of graphene most likely from heteroatoms induced by the substrate using Raman spectra, x-ray photoelectron spectroscopy, energy dispersive x-ray spectroscopy and ab initio molecular dynamics (MD) simulations. The doping of graphene on a highly boron-doped silicon substrate was achieved by an annealing at 400 K for about 3 h in an oven with air flow. With the same annealing, only the Raman features similar to that from the pristine graphene were observed in the freestanding graphene and the graphene on a typical Si/SiO2 wafer. Ab initio MD simulations were performed for defected graphene on boron-doped silicon substrate at several temperatures. All vacancy sites in the graphene are occupied either with B atoms or Si atoms resulting in the mixed boron–silicon doping of the graphene. The MD simulations validated the experimetal finding of graphene doped behavior observed by Raman spectrum. The electronic structure analysis indicated the p-type nature of doped graphene. The observed doping by the possible incorporation of heteroatoms into the graphene, simply only using 400 K annealing the boron-doped Si substrate, could provide a new approach to synthesize doped graphene in a more economic way.